MEDIA DISCOURSE: A PRAGMA-STYLISTIC ANALYSIS OF SOCIAL MEDIA ADVERTISEMENTS IN PAKISTAN - Muhammad Manzoor Alam; Dr. Zulfiqar Ali; Muhammad Sufyan Khan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This paper is aimed at investigating the role of speech acts and choice of distinctive language style in understanding the hidden message in advertisements through using pragma-stylistic analysis approach. The Pragmatic-Stylistic approach is a language strategy that focuses on the linguistic abilities of interlocutors to convey the intended meaning, as well as the speaker's own distinctive style of conveying a piece of information. The data consists of nine advertisements collected online from social media forums such as Facebook, YouTube, Instagram, and Twitter. The first three advertisements are about beauty products, the fourth, fifth and sixth advertisements are about health products, and the last three advertisements are regarding food products. The discourse and linguistic style of social media advertisements is analysed with the help of speech act theory, textual conceptual functions, and AIDA (Attention, Interest, Desire and Attention) principles. The analysis concludes that by employing different linguistic devices, sounds, rhymes, figurative language, graphology, speech acts and AIDA principles, the advertisers attract the people and reach to their ultimate goal, which is to sell their products. This study contributes in the field of media discourse analysis and pave a path for other researchers to conduct studies in the field.